Robotic surgical procedure for diffuse cavernous hemangioma of the rectum: A case report. Issue 4 (20th January 2020) - Fujii, Yoshiaki; Kobayashi, Kenji; Kimura, Syo; Tsuji, Eri; Miyai, Hirotaka; Tanaka, Moritsugu; Takiguchi, Shuji
Abstract: Diffuse cavernous hemangioma of the rectum (DCHR) is a relatively rare benign vascular disease. DCHR is marked by recurrent bleeding and anemia, and it is difficult to diagnose correctly. Here, we report the case of a 34‐year‐old man diagnosed with DCHR by colonoscopy, CT, and endoscopic ultrasonography. The patient underwent a robot‐assisted anterior abdominal excision and subsequently recovered well from the surgery. Ileostomy closure was performed 3 months after surgery. Eight months after surgery, he had no evidence of rectal bleeding, and his defecation function was good, with no fecal incontinence. Regardless of the characteristics of DCHR and the susceptible age of DCHR, it is important to diagnose DCHR correctly as soon as possible and to treat it without a permanent colostomy. Robot‐assisted resection may be a good option for the treatment of DCHR.